Risk factors for lower extremity deep vein thrombosis in acute stroke patients following endovascular thrombectomy: a retrospective cohort study - Han, Li; Yang, Jian-Miao; Qian, Wei-Yang; Xu, Xiao-Ping; Tung, Tao-Hsin; Liu, Yang; Wang, Feng (Frontiers in Neurology, 2023)
Background Deep vein thrombosis (DVT) in lower extremities as a common complication of acute ischemic stroke (AIS) has long been studied. However, as the therapeutic options for AIS continue to advance, the pathogenic mechanisms behind DVT may change. Endovascular thrombectomy (EVT) has replaced intravenous thrombolysis and become the preferred treatment for AIS patients with large vessel occlusions. Therefore, it is important to update our understanding of DVT and its management. This study aimed to determine the prevalence and risk factors of DVT in AIS patients following EVT. Methods In this retrospective study, 245 AIS patients who had received EVT were recruited between January 2020 and December 2021. Within 10 days (median 4 days) of thrombectomy, DVT was diagnosed by ultrasonography. Demographic characteristics, clinical findings, and therapeutic procedures were compared between patients with and without DVT using univariate analysis. Cutoff points were defined for EVT time and plasma D-dimer concentration. Multivariable logistic regression was then used to determine the independent risk factors for DVT and evaluate their predictive power. Results The prevalence of DVT in AIS patients after EVT was 27.3%. Multifactorial logistic regression analysis showed that age (OR 1.036, 95% CI 1.001–1.073; P = 0.045), female sex (OR 3.015, 95% CI 1.446–6.289; P = 0.003), lower limb muscle strength less than grade three (OR 7.015, 95% CI 1.887–26.080; P = 0.004), longer EVT time (OR 1.012, 95% CI 1.004–1.020; P = 0.003), and higher D-dimer levels (OR 1.350, 95% CI 1.150–1.585; P < 0.001) were independently associated with higher DVT risk in AIS patients following EVT. The cutoff points for operative time of EVT and plasma D-dimer were 65.5 min and 1.62 mg/L, respectively, above which the risk for DVT was dramatically increased with OR > 4 in AIS patients. Conclusion AIS patients are at increased risk of developing DVT following EVT particularly if they have undergone prolonged thrombectomy procedures and exhibit high plasma levels of D-dimers. However, the results of our study need to be validated by a multicenter prospective study with a larger population of stroke patients.